Improving Conceptual Understanding of Mathematics Through Blended Learning Using Google Classroom - Walid, Abul (International Journal of Education and Teaching Zone, 2023)
The 2018 PISA results recommend increasing learning achievement by improving teaching quality and learning climate. Responding to these recommendations, it is necessary to improve the quality of teaching and student learning climate, one of which is applying blended learning. This pre-experimental study aims to determine the increased conceptual understanding of mathematics through blended learning using Google Classroom. This study used one group pretest-posttest design, and data were collected through a test of conceptual understanding of mathematics. This research involved 14 junior high school students. Descriptive statistic effect size and inferential t-tests are used in analyzing research data. The research results show a difference in the average score in conceptual understanding of mathematics before and after applying Blended learning using Google Classroom. In other words, it is empirically proven that conceptual understanding of mathematics can be improved through Blended learning using Google Classroom with a magnitude of effect increase of 76%. In comparison, 24% were influenced by other factors.